Multi-source recovered graphite and its use in electrodes for energy storage - Zensich, Maximiliano Andres (2023)
This review summarises the latest improvements in the recovery of graphite to be used in electrochemical energy storage (EES) devices, without limiting to lithium-ion batteries as the only source and final destination of graphite. The work is focused on the characteristics of graphite recycled by different processes and its effect on the electrochemical behaviour of the application. An analysis of the advantages and disadvantages of each method was carried out considering factors related to the environment, cost, and usefulness of the recovered material. Finally, some challenges and our perspectives are outlined.